Sulfur supply reduces cadmium uptake and translocation in rice grains (Oryza sativa L.) by enhancing iron plaque formation, cadmium chelation and vacuolar sequestration. (July 2018) - Cao, Zhen-Zhen; Qin, Mei-Ling; Lin, Xiao-Yan; Zhu, Zhi-Wei; Chen, Ming-Xue
Abstract: Sulfur (S) fertilizer application in rice ( Oryza sativa L.) is crucial in determining rice grain productivity and quality. However, little information is available concerning the effect of S supply on cadmium (Cd) uptake and translocation in rice. In this study, both hydroponic and soil experiments were conducted to investigate the influence of S supply on Cd accumulation in rice under two Cd levels (0 and 50 μM), combined with three S concentrations (0, 2.64 and 5.28 mM). The moderate and excessive S supply (2.64 and 5.28 mM) tended to increase plant growth, root length, root and shoot dry weights of rice seedlings, and significantly decreased Cd concentrations in rice plants and grains in the absence or presence of Cd. The subcellular distribution and chemical forms of Cd in roots and shoots also varied with S supply levels. The decreased Cd uptake and translocation in rice grains could be ascribed to the enhanced formation of iron (Fe) plaque on the root surfaces and increased Cd chelation and vacuolar sequestration in roots, since Fe, Mn concentrations in Fe plaque, glutathione and phytochelatins contents, as well as phytochelatin synthase ( OsPCS ) and tonoplast heavy metal ATPase ( OsHMA3 ) expressions in roots significantly increased with increased S supply. This work provides more insight into the mechanisms of Cd uptake and translocation in rice, and will be helpful for developing strategies to reduce rice grain Cd through S fertilizer application in Cd-contaminated soil. Graphical abstract: Image 1 Highlights: S supply reduces health risk to humans by decreasing Cd accumulation in rice grains. S supply restrains Cd uptake by enhancing Fe plaque formation on the root surfaces. S supply reduces Cd translocation by increasing Cd chelation and vacuolar sequestration in roots.